Leprosy, Water, Sanitation, and Hygiene: A Case–Control Study in a Hyperendemic Area of Brazil - Tolulope R. Ojo-Akosile; Lorena B. P. de Oliveira; Rosemary K. e Lima; José A. Ferreira; Julie A. Clennon; Alexandre C. Branco; Erica B. M. Silva; Maria Aparecida de Faria Grossi; Lucia A. O. Fraga; Jessica K. Fairley (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Viable Mycobacterium leprae has been detected in the environment and there is growing evidence that the environment may play a role in transmission. Our objective, therefore, was to further explore the association of insecure water, sanitation, and hygiene (WASH) and leprosy in a hyperendemic area of Brazil. A case–control study was conducted in eastern Minas Gerais, Brazil, between June 2016 and December 2018. Individuals with newly diagnosed leprosy and controls ages 3 years or older were enrolled. A demographic and WASH questionnaire was administered, and blood and stool collected for helminth diagnoses. Descriptive, bivariate, and multivariable analyses were conducted. Seventy-nine cases and 81 noncontact controls were recruited. The mean age was 40, and 52% were male. Most (75% [ n = 120]) had piped water, 112 (71%) had a household piped sewer system, and 45 (29%) used a latrine or other type of sanitation system. Leprosy was associated with larger household sizes (adjusted odds ratio [aOR] = 1.34; 95% CI: 1.07–1.68], and, unexpectedly, with an improved household sewer system (aOR = 4.67; 95% CI: 1.51–14.45). Those with leprosy were also less likely to use piped water for drinking (aOR = 0.39; 95% CI: 0.13–1.18) or to treat their water (aOR = 0.52; 95% CI: 0.25–1.06), although these did not reach statistical significance. Although the positive association with a piped sewer system was unexpected, the findings suggest that WASH factors could be related to leprosy in this context, and further investigation into potential mechanisms for exposure is warranted.